Electrochemical triamination of alkynes: controllable synthesis of functionalized indolines and indoles. Issue 12 (30th May 2022) - Meng, Xiangtai; Xu, Hehua; Liu, Rui; Zheng, Yu; Huang, Shenlin
Abstract : The electrochemical triamination of alkynes has been developed, affording a variety of 2, 3-diimino indolines and 2, 3-diamino indoles. Abstract : Electrochemically generated N-radicals are powerful reactive intermediates to construct N-heterocycles. However, these N-centered radicals have never been employed in the trifunctionalization of alkynes. We herein report an unprecedented electrocatalytic triamination of alkynes via N–H cleavage, enabling controllable access to a variety of 2, 3-diimino indolines and 2, 3-diamino indoles. This sustainable strategy employs 2, 2, 6, 6-tetramethylpiperidinooxy (TEMPO) as the redox catalyst and avoids the undesirable use of terminal oxidants, transition metals, and explosive reagents. Mechanistic investigations suggest that this triamination reaction might proceed via 5- endo-dig cyclization of a N-centered radical and two successive radical couplings with a nitrenium intermediate. Furthermore, this triamination strategy concurrently assembles indole scaffolds and two additional amino substituents from readily available anilines, and therefore rapidly increases molecular complexity allowing further synthetic transformations of the 2, 3-diamino indole core.